2010
DOI: 10.1007/s00264-010-1071-z
|View full text |Cite
|
Sign up to set email alerts
|

Double calcaneal osteotomy and percutaneous tenoplasty for adequate arch restoration in adult flexible flat foot

Abstract: Treatment of adult acquired flexible flat foot deformity can be problematic. Triple arthrodesis for structural correction has been the standard of care, thus sacrificing hind foot motion. The objective of this study was to assess the value of double calcaneal osteotomies in improving structural alignment while maintaining hind foot motion, which may further protect the function of adjacent motion segments. Double calcaneal osteotomies (Evans osteotomy and posterior calcaneal displacement osteotomy) were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…23 Short-term follow-up of calcaneal osteotomies has shown clear gains in foot function measured with the AOFAS scale. 2 In a long-term follow-up study (mean 51 months; range 38-62 months), open calcaneal osteotomies were reported to improve the AOFAS score from 48.8 preoperatively to 85.5 postoperatively, and to have a reduction in the VAS scores from 7.3 to 1.7. 23 The reported improvements in the pre- and postoperative (3-5 year) VAS scores are comparable to the short-term improvements in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…23 Short-term follow-up of calcaneal osteotomies has shown clear gains in foot function measured with the AOFAS scale. 2 In a long-term follow-up study (mean 51 months; range 38-62 months), open calcaneal osteotomies were reported to improve the AOFAS score from 48.8 preoperatively to 85.5 postoperatively, and to have a reduction in the VAS scores from 7.3 to 1.7. 23 The reported improvements in the pre- and postoperative (3-5 year) VAS scores are comparable to the short-term improvements in our study.…”
Section: Discussionmentioning
confidence: 97%
“…By restoring foot alignment and the weight bearing axis it has been shown that not only are peak pressures diminished in the hindfoot, but functional outcomes can be significantly improved in a variety of pathologies. 2,10,11…”
mentioning
confidence: 99%
“…A variety of fixation techniques have been reported for the double calcaneal osteotomy (1,2,8,9,11). However, revision is often required because of pain caused by bony nonunion (12).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple investigators have discussed using a 3.5-mm cortical screw across the Evans osteotomy site combined with two parallel 6.5-mm cancellous screws across the medial displacement calcaneal osteotomy site (7,8). Other investigators have detailed the use of two percutaneous Kirschner wires (9). In addition, successful outcomes with the use of unilateral rail external fixation have been documented (10).…”
mentioning
confidence: 99%
“…We report the outcomes of double calcaneal osteotomy for severe adolescent flexible flatfoot reconstruction, which was rarely reported before. Limited articles reported the outcomes of double calcaneal osteotomy for treatment of adult flatfoot [ 5 7 ], and there is no article reported this method used in adolescent patients. In this study, all patients were older than 14 with hindfoot valgus angle larger than 15° and talonavicular coverage angle larger than 20°.…”
Section: Introductionmentioning
confidence: 99%